Ekspresi Fatis Melayu Belitung - JASMINE, MUTIARA; FAUZIAH, ESKA ROJWA; AINA, NADIFA NURUL; MAISARI , NAZWA MIRDA (TALENTA, 2026)
Belitung Malay, known as Base Belitung, is a Malay dialect variety spoken by hundreds of thousands of indigenous inhabitants of Belitung Island. Despite its significant number of speakers, studies on phatic elements in this dialect remain limited. This study aims to describe phatic categories, including particles, phrases, and expressions that maintain social relationships, emphasize meaning, and enhance interpersonal interaction. Data were collected through recordings of natural conversations and in-depth interviews with ten proficient speakers. Analysis focused on the pragmatic function of each phatic element. The findings reveal a range of distinctive phatic particles, including eh, jok, tek, yee, an, wai, mak, nang, be, e, lah, and kan, each serving a specific function. This study contributes to regional linguistic documentation, preservation of oral cultural heritage, and enrichment of Malay dialect research, while highlighting the crucial role of phatic elements in fostering harmonious communication within the Belitung community.